The Legal Perspective of Blockchain’s Potential Use for Sharia Banking Institutions in Indonesia - Uni Tsulasi Putri; Nikmah Mentari (Hang Tuah Law Journal, 2022)
In nowadays era, sharia banking shall face many challenges. Sharia banking shall be able to create innovation and disruption to avoid being eroded by current development. Blockchain is one of the technology disruptions. It may potentially applicable within sharia finance industry including sharia banking, outside its use related to the sale and purchase of crypto asset. This research discusses on how to use blockchain technologi for the development of sharia banking as well as on what are the opportunity and challenges in applying blockchain for sharia banking in Indonesia. This is a normative legal research with using descriptive-qualitative data analysis method. Data in this research is secondary data which consist of primary legal sources and secondary legal sources. The former are laws and regulations related to blockchain and sharia banking. The latter are books, academic writings, journals and other primary-source-explanatory documents. The results in this research show that sharia finance industry especially banking can utilize blockchain such as by using its smart contract, for the collection of zakat, improvement of waqf utility, effective and efficient halal supply chain. The opportunity of blockchain are there have been OJK and BI regulation concerning blockchain in certain area, support of blockchain development manifested in Sharia Economic Masterplan, demographic bonus in Indonesia, the use of smart contract, the use of blockchain for supporting halal supply chain, zakat collection, waqf utility, as well as the security guarantee in minimalizing fraud risk. Among others, the challenges blockchain shall face are, the policy and regulations of blockchain are still limited to only in some sectors such as payment and equity crowdfunding, there is no fatwa from MUI (Indonesian Ulema Board) regarding the use of blockchain for sharia economic activities, and the complexity of blockchain.